Do the endocrine and subjective effects of d-fenfluramine predict response to selective serotonin reuptake inhibitors? - Park, S; Williamson, D; Cowen, P (1995)
Thirty drug-free depressed patients underwent double-blind, placebo-controlled, neuroendocrine testing with the serotonin (5-HT) releasing agent d-fenfluramine prior to receiving treatment with a selective serotonin reuptake inhibitor (SSRI) for 8 weeks. Compared to placebo, d-fenfluramine significantly elevated plasma levels of prolactin and cortisol, increased subjective visual analogue ratings of "light headed" and decreased ratings of "desire to eat". Of the 30 patients studied, 17 responded to treatment but none of the pretreatment responses to d-fenfluramine distinguished patients who responded to SSRI treatment from those who did not. The results suggest that the clinical response to SSRI administration may be independent of pretreatment brain 5-HT function. Another possibility is that the neuroendocrine and subjective effects of d-fenfluramine are mediated by 5-HT mechanisms other than those involved in the antidepressant effect of SSRIs.